Utilization of Taro (Colocasia esculenta) as a Bacterial Growth Medium Supporting Microbiology Laboratory Independence Based on Local Papuan Food Resources - Sarima Sarima; Makmum Ashari; Rimba Lukas Kiding; Estervina Ribka Ance Yoku (Universitas Labuhanbatu, 2025)
Background: In universities, the availability of bacterial growth media, which is typically synthetic media such as Nutrient Agar (NA), is extremely important for microbiology practicum activities. Nevertheless, in eastern Indonesia, such as Papua, the high cost of commercial media, the reliance on distribution from outside the region, and the limited budget and laboratory facilities frequently present obstacles to access. Currently, there is a significant lack of research on the use of Papuan local food resources as an alternative medium for bacterial growth. Consequently, further research is required to address this gap. The objective of this investigation is to investigate the potential of taro (Colocasia esculenta), a local source of Papuan carbohydrates, as the foundation for the development of an alternative medium for the growth of Escherichia coli bacteria. This is due to the amylose content of 20–25% and amylopectin of 75–80%, which have the potential to serve as an energy source for bacteria. Method: The media was made from taro extract formulated with the addition of agar, glucose, and MSG, then sterilized and inoculated with E. Coli bacteria. The data were analyzed using the parameters of the number of colonies (CFU/mL) with the ALT calculation standard, as well as a descriptive comparison between the control medium (NA) and the taro media. Results: The Taro alternative media is capable of supporting bacterial growth at a rate of 8.3 × 10⁶ CFU/mL, which is approximately 75.5% of the NA media's capacity of 11 × 106 CFU/mL. Although the color of the colonies differs slightly, the morphological characteristics of colonies growing in alternative media are similar to those of colonies in NA media in terms of shape, elevation, size, and edges. Conclusions: These findings indicate that taro has significant potential as a substitute for microbiological media that is based on local resources. Not only does the utilization of this medium offer practical and cost-effective solutions for laboratory activities, but it also promotes educational independence and innovation that are rooted in local knowledge in restricted regions. The implications of this research provide opportunities for laboratory independence in the 3T area and promote the utilization of local wisdom for sustainable microbiology research and education